2015
DOI: 10.1080/13632469.2015.1051638
|View full text |Cite
|
Sign up to set email alerts
|

Application of In-Test Model Updating to Earthquake Structural Assessment

Abstract: Analytical methods are frequently utilized for structural assessment due to their simplicity and costeffectiveness. However, modeling of material inelasticity and geometric nonlinearity under reversed inelastic deformations is still very challenging and its accuracy is difficult to quantify. On the other hand, realistic experimental assessment is costly, time-consuming, and impractical for large or spatially extended structures. Hybrid simulation has been developed as an approach that combines the realism of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…They can feature the desirable simulation of the observed kinematic and isotropic hardening phenomena. [14][15][16][17][18][19][20] In hybrid simulation, also called hybrid testing, [21][22][23][24][25][26][27][28][29] the target structure can be partitioned into multiple substructures. When constitutive models such as the Bouc-Wen model and the 2-surface model are adopted in nonlinear structural response simulations, the lack of relations between the control parameters and the mechanical properties may result in difficulties in finding the parameter values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They can feature the desirable simulation of the observed kinematic and isotropic hardening phenomena. [14][15][16][17][18][19][20] In hybrid simulation, also called hybrid testing, [21][22][23][24][25][26][27][28][29] the target structure can be partitioned into multiple substructures. When constitutive models such as the Bouc-Wen model and the 2-surface model are adopted in nonlinear structural response simulations, the lack of relations between the control parameters and the mechanical properties may result in difficulties in finding the parameter values.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional model fitting is done using the trial and error method. [14][15][16][17][18][19][20] 2.2 | Analytical model for the BRB In order to improve the efficiency of model fitting, various techniques for parameter identification were developed in the past years.…”
Section: Overview Of Parameter Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial neural networks could be utilized for nonlinear model updating, but in some cases, only consideration of dynamic responses for model updating may lead to incorrect parameter predictions, and both static and dynamic responses should be used together in model updating . Moreover, modeling of material inelasticity and geometric nonlinearity under reversed inelastic deformations is still challenging, and its accuracy is difficult to quantify . It is shown that the uncertainty due to nonlinear effects is hardly comprehensible in comparison with other measurement uncertainties in dynamic experiments .…”
Section: Proposed Methodsmentioning
confidence: 99%
“…However, if only one physical specimen is constructed and tested while all other relevant elements are numerically simulated, the advantages of HS would be significantly diminished due to the inaccurate modeling of the not‐well‐understood substructures with numerical approach. To address this issue, the development of the online model updating (OMU) technique has gained increasing attention in recent years . One effective approach for OMU is adopted in a series of hybrid tests presented in this paper.…”
Section: Introductionmentioning
confidence: 99%